ANALYSIS OF FINANCIAL FULFILLMENT OF VANAME (LITOPENAEUS VANNAMEI) GROWING INTENSIVE SYSTEMS AT THE MINA JAYA TAMIANG FARMING GROUP VILLAGE DAGANG SETIA MANYAK PAYED DISTRICT ACEH TAMIANG - Mahnasya, Fazlia; Saragih, Faoeza Hafiz; Jamil, Muhammad (Syarif Hidayatullah State Islamic University Jakarta, 2023)
Intensive Vaname Shrimp farming requires higher costs compared to traditional systems. With a high stocking density, intensive system vaname shrimp farming can produce high shrimp production. So with this fact, intensive system vaname shrimp farming can be applied by the community, especially people in Aceh Tamiang District. This research was conducted at Pokdakan Mina Jaya Tamiang, Dagang Setia Village, Manyak Payed District, Aceh Tamiang Regency. The purpose of the study was to determine the financial feasibility of raising vaname shrimp in Pokdakan Mina Jaya Tamiang, Dagang Setia Village, Manyak Payed District, Aceh Tamiang Regency. This research uses case studies and analyzed descriptively quantitative. Determination of the sample using purposive sampling technique. The analysis calculated is Net Present Value (NPV), Net B / C Ratio, Internal Rate Return (IRR), and Break Event point (BEP). The results showed that the NPV obtained was 3,463,203,705 greater than 0; IRR obtained was 67.37% greater than the interest rate of 10.5%; Net B / C ratio value obtained was 2.72 greater than 1; Production BEP was 38,490 kg; And BEP price was Rp.37,615. So it can be concluded that the Vaname Shrimp Enlargement Business (Litopenaeus vannamei) Intensive System in Pokdakan Mina Jaya Tamiang Pond is profitable and feasible to run.